Biodegradation of Atrazine Herbicide: A Mini-review (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Atrazine herbicide is known to disrupt the endocrine system and is potentially carcinogenic. The long-term use of this herbicide results in high residue levels in soil, causing water contamination of agricultural land. Microbial degradation of herbicide represents a cost-effective way of eco-restoration compared to the more expensive physicochemical methods, especially in soil settings. Growth and degradation of atrazine by microorganisms are optimal at specific concentrations, temperature, pH, inoculum size and hours of incubation. Previously isolated microorganisms have demonstrated high efficiency for atrazine biodegradation with a broad optimum pH and temperature. The metabolic pathway for biodegradation has been elucidated and reveals important characteristics. These organisms as suitable candidates for bioremediation of atrazine-polluted sites have shown great potential for atrazine degradation.  This review aimed to catalogue and update the characteristics of isolated atrazine-degrading microorganisms to date.
Keywords: Atrazine; Bacteria; Bioremediation; Biodegradation; Pollution